The long road of war : a marine's story of Pacific combat - Johnston, James W., 1922-2009 (University of Nebraska Press, 1998)
James W. Johnston was a self-confessed small-town youth, who like so many others patriotically stopped what he was doing and enlisted shortly after Pearl Harbor. Johnston chose the Marines, a decision that sent him to years of bloody combat through the Pacific, as Allied troops fought their way toward the Japanese home islands.